Ethical considerations when conservation research involves people. Issue 4 (15th April 2020) - Brittain, Stephanie; Ibbett, Harriet; de Lange, Emiel; Dorward, Leejiah; Hoyte, Simon; Marino, Agnese; Milner‐Gulland, E. J.; Newth, Julia; Rakotonarivo, Sarobidy; Veríssimo, Diogo; Lewis, Jerome
Abstract: Social science is becoming increasingly important in conservation, with more studies involving methodologies that collect data from and about people. Conservation science is a normative and applied discipline designed to support and inform management and practice. Poor research practice risks harming participants and, researchers, and can leave negative legacies. Often, those at the forefront of field‐based research are early‐career researchers, many of whom enter their first research experience ill‐prepared for the ethical conundrums they may face. We draw on our own experiences as early‐career researchers to illuminate how ethical challenges arise during conservation research that involves human participants. Specifically, we considered ethical review procedures, conflicts of values, and power relations, and devised broad recommendations on how to navigate ethical challenges when they arise during research. In particular, we recommend researchers apply reflexivity (i.e., thinking that allows researchers to recognize the effect researchers have on the research) to help navigate ethical challenges and encourage greater engagement with ethical review processes and the development of ethical guidelines for conservation research that involves human participants. Such guidelines must be accompanied by the integration of rigorous ethical training into conservation education. We believe our experiences are not uncommon and can be avoided and hope to spark discussion to contribute to a more socially just conservation. Abstract : Article Impact Statement : Researchers must go beyond formal ethical protocols to protect participants, researchers, and the integrity of conservation research. Abstract : Consideraciones Éticas cuando la Investigación para la Conservación Involucra a la Gente Resumen: Las ciencias sociales cada vez son más importantes para la conservación pues más estudios involucran metodologías que recolectan datos de y sobre la gente. La ciencia de la conservación es una disciplina normativa y aplicada diseñada para apoyar e informar al manejo y a la práctica. La investigación deficiente corre el riesgo de dañar a los participantes y a los investigadores, además de que puede dejar un legado negativo. Es común que investigadores que recién inician sus carreras estén al frente de investigación basada en el campo, muchos de los cuales comenzaron su experiencia mal preparados para los dilemas éticos que podrían enfrentar. Partimos de nuestras propias experiencias como investigadores de carrera temprana para ilustrar cómo emergen los retos éticos durante la investigación para la conservación que incluye a participantes humanos. Específicamente, consideramos los procedimientos de revisión ética, los conflictos de valores y las relaciones de poder y con ellas diseñamos recomendaciones de comité sobre cómo navegar los retos éticos cuando surjan durante la investigación. Particularmente, recomendamos a los investigadores que apliquen la reflexividad (es decir, el pensamiento que permite a los investigadores reconocer el efecto que ellos tienen sobre la investigación) para ayudar a navegar los retos éticos y para alentar un mayor compromiso con los procesos de revisión ética y con el desarrollo de las directrices éticas para la investigación de la conservación que involucra a participantes humanos. Dichas directrices deben estar acompañadas por la integración de un entrenamiento ético riguroso dentro de la educación para la conservación. Creemos que nuestras experiencias no son poco comunes y pueden evitarse y esperamos iniciar una discusión para contribuir a una conservación más justa socialmente. 摘要: 随着越来越多的保护研究采用收集来自人类或与人类有关数据的研究方法, 社会科学在保护中也变得越来越重要。保护科学是一门规范性的应用学科, 旨在为管理和实践提供支持和信息。然而, 不当的研究实践有可能伤害参与者和研究人员, 并产生负面的遗留问题。通常, 参与实地研究的一线人员都是处于职业生涯早期的研究者, 其中许多人在第一次进行研究时对可能面临的伦理问题没有充分准备。我们利用自身作为青年研究者的经验, 阐明了在涉及人类参与的保护研究中存在哪些伦理挑战。具体来说, 我们分析了伦理审查过程、价值观冲突和权力关系, 并就如何应对研究中出现的伦理挑战提出了普遍的建议。我们特别建议研究者应用反身性)也就是使研究者认识到其自身对研究影响的思考(来帮助应对伦理挑战, 我们还鼓励研究者更多地参与伦理审查过程, 并为涉及人类参与者的保护研究制定伦理指南。在制定指南的同时, 必须将严格的伦理训练纳入保护教育。我们相信我们的经历并非罕见且可以避免, 希望本研究能引发讨论, 从而为更具社会公平性的保护做出贡献。【翻译: 胡怡思; 审校: 聂永刚】